Efficient use of Monte Carlo: the fast correlation coefficient - Sjöstrand Henrik; Asquith Nicola; Helgesson Petter; Rochman Dimitri; Marck Steven van der (EPJ Nuclear Sciences & Technologies, 2018)
Random sampling methods are used for nuclear data (ND) uncertainty propagation, often in combination with the use of Monte Carlo codes (e.g., MCNP). One example is the Total Monte Carlo (TMC) method. The standard way to visualize and interpret ND covariances is by the use of the Pearson correlation coefficient,